Hydroponic green corn fodder as a supplement to calves in dry season - Castellanos-Arellanes, Ismael; Alaniz Gutiérrez, Luis; Rojas-García, Adelaido Rafael; Cisneros-Saguilán, Pedro; Bottini-Luzardo, María Benedicta; Mendoza-Núñez, Mario Antonio (Ecosistemas y Recursos Agropecuarios, 2025)
Bovine livestock in the tropical areas of the state of Guerrero faces several challenges, particularly forage shortages during the dry season, which lead to economic losses, weight loss, and animal mortality. The objective of this study was to evaluate the use of hydroponic green corn forage (FVHM) as a supplementary feed alternative for calves during the drought season in Cuajinicuilapa, Guerrero, Mexico. The bromatological and productive characteristics of the FVHM were evaluated at 10, 15 and 20 days after sowing. Consumption, daily weight gain and ruminal characteristics of 15 calves supplemented with different inclusion levels of FVHM were measured. The experimental design was completely randomized, and mean differences were analyzed using Tukey´s test (p < 0.05). The forage harvested on day 15 exhibited the best characteristics with 16.6% CP, a height of 23.6 cm and a yield of 6.64 kg per kg of germinated seed. In the in vivo experiment, no statistical differences were found between treatments (p > 0.05); however, the treatment with 40% FVHM inclusion was numerically superior, influencing the cost analysis, where it showed higher profitability and a benefit-cost ratio of 1.15, outperforming the other treatments. It is concluded that the FVHM production is viable at the local level and represents a promising option for incorporation into cattle diets.